PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra, R. Adhi Kusuma (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of Current Ratio (CR), Debt to Equity Ratio(DER), and Return on Assets(ROA) to the stock return at manufacturing companies which engage in the field of food and beverage industry are listed in the Indonesia Stock Exchange (IDX) both simultaneously and partially. The hypothesis in this research are: (1) there is CR influence to the stock return, (2) there is no DER influence to the stock return, (3) there is ROA influence to the stock return.The populations in this research are manufacturing companies which engage in the field of food and beverage industry are listed in the Indonesia Stock Exchange of 2010 â 2012 periods in which the populations are 16 companies. Purposive sampling is used as the sample collection technique and the samples are 10 samples. Secondary data is used as the data in this research. Multiple regression analysis is carried out by performing classic assumption test is used as the examination method in this research.The result of analysis shows that financial ratios which consist of CR, DER, and ROA ratios simultaneously have influence while partially CR and DER have no significant influence to the stock return whereas ROA has significant influence to the stock return of manufacturing companies which engage in the field of food and beverage are listed in the Indonesia Stock Exchange. Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets and Stock Return